Self-rated physical attractiveness and its relation to psychological well-being across adolescence. Issue 4 (4th July 2022) - Raible-Destan, Nesrin; Stulz, Niklaus; Hepp, Urs; Ribeaud, Denis; Eisner, Manuel; Steinhoff, Annekatrin; Shanahan, Lilly; Sell, Aaron; Kupferschmid, Stephan
ABSTRACT: The goal of the current analyses was to explore associations of self-rated physical attractiveness with facets of psychological well-being across adolescence. Participants provided information on their perceived physical attractiveness, internalized distress, suicidal ideation, and self-harm at 15, 17 and 20 years of age. Male adolescents repeatedly provided higher ratings of their own physical attractiveness in comparison to female peers. Self-perceived physical attractiveness was negatively associated with internalized distress in 15- to 20-year-old girls. In boys this association reached statistical significance only at the ages of 17 and 20 years. Statistically significant relations between suicidal ideation, self-harm and physical attractiveness resulted in girls only. Findings suggest small but stable relationships between self-rated physical attractiveness and facets of psychological well-being between 15 and 20 years – particularly in girls. Results underline the importance of self-perceived attractiveness in relation to mental health across adolescence.